Manhaj Ta’lim al-Nahwi wa al-Sharfi fi Ma’hadi Dar al-‘Arafah Raya Deli Serdang Sumatra al-Shamaliya - Nadlrah Naimi; Melyani Sari Sitepu; Imam Rinaldi (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2022)
This study aims to: 1) find out the methods used in learning Nahwu and Sharaf Sciences at the Darularafah Raya Islamic Boarding School, 2) find out the supporting and inhibiting factors in learning Nahwu and Sharaf Sciences at the Darularafah Raya Islamic Boarding School, 3) Efforts made to overcome obstacles in the study of Nahwu and Sharaf Sciences at the Darularafah Raya Islamic Boarding School. This research is a qualitative research. In this study, the data collection techniques used are; observation, interview and documentation. The results showed that: 1) The Nahwu and Sharaf learning methods applied by the Darularafah Raya Islamic Boarding School in the teaching and learning process were quite good, this could be seen from the teacher's efforts in improving the learning methods used. 2) In this case the teacher uses two kinds of methods, namely deductive and inductive in Nahwu lessons and memorization methods in Sharaf lessons. 3) In a learning process there will definitely be factors that support and factors that hinder a learning process. The factors in question are divided into two, namely internal factors and external factors. 4) Regarding the efforts taken by the teacher in overcoming the inhibiting factors experienced by students in learning nahwu and sharaf at the Darularafah Raya Islamic Boarding School as follows; provide motivation to students, fix the learning system both in terms of objectives, methods, media, strategies used in the learning process, always provide opportunities for students to improve their understanding of the science of nahwu sharaf.